A feasibility randomised controlled trial of a brief early intervention for adolescent depression that targets emotional mental images and memory specificity (IMAGINE). (August 2021) - Pile, Victoria; Smith, Patrick; Leamy, Mary; Oliver, Abigail; Bennett, Eleanor; Blackwell, Simon E.; Meiser-Stedman, Richard; Stringer, Dominic; Dunn, Barnaby D.; Holmes, Emily A.; Lau, Jennifer Y.F.
Abstract: Brief, evidence-based interventions for adolescent depression are urgently required, particularly for school-settings. Cognitive mechanisms research suggests dysfunctional mental imagery and overgeneral memory could be promising targets to improve mood. This feasibility randomised controlled trial with parallel symptomatic groups (n = 56) compared a novel imagery-based cognitive behavioural intervention (ICBI) to non-directive supportive therapy (NDST) in school settings. Blind assessments (of clinical symptoms and cognitive mechanisms) took place pre-intervention, post-intervention and follow-up three months later. The trial aimed to evaluate the feasibility and acceptability of the methodology and interventions, and estimate the likely range of effects of the intervention on self-reported depression. The pre-defined criteria for proceeding to a definitive RCT were met: full recruitment occurred within eleven months; retention was 89%; ICBI acceptability was above satisfactory; and no harm was indicated. Intention-to-treat analysis found large effects in favour of ICBI (relative to NDST) at post-intervention in reducing depressive symptoms (d = −1.34, 95% CI [-1.87, −0.80]) and improving memory specificity (d = 0.79 [0.35, 1.23]), a key cognitive target. The findings suggest that ICBI may not only improve mood but also strengthen abilities associated with imagining and planning the future, critical skills at this life stage. A fully powered evaluation of ICBI is warranted. Trial Registration: https://www.isrctn.com/ ; ISRCTN85369879. Highlights: Trial evaluated a mechanistically focused intervention for adolescent depression. Imagery-based intervention (ICBI) compared to non-directive supportive therapy. All continuation rules were met for feasibility and acceptability. Large between group differences in depressive symptoms and memory specificity. Definitive trial indicated to determine treatment efficacy of ICBI.